Voice over internet protocol in small and medium enterprises - Rigo, Ricardo C.; Imbang, Prof. Glen; Cruz, Prof. Edison (Quezon City University of the Philippines Diliman, 2009)
Part 1 of this report discusses the objectives that the project aims to achieve, which is to develop a business case for Voice Over Internet Protocol (VOIP) in Small and Medium Enterprises (SMEs). The slow adoption of VOIP, despite known benefits, and the reasons behind its slow adoption, were among the problems and opportunities that need to be addressed. The importance of the project outputs to different stakeholders is stated in the project significance section. In the methodology, the researcher identified the different research methodologies that have been employed for this research project; library and internet research, conduct of a survey, and forecasting using PEST analysis. Lastly, the framework used in conducting this project was also discussed in this chapter. Part 2 - VOIP Technology discusses the definition and benefits of the technology. It also presents an outline of the historical development of the technology. Practical applications were identified in later sections, along with the issues and challenges that come with its implementation. Major issues identified were reliability, quality of service, legal and regulatory and security issues. SMEs in the country are discussed in Part 3. It includes the definition of SMEs, classification according to size of assets or size of organization, the technological capability of SMEs to adopt information and communications technology, and the barriers to said adoption that are prevalent in most SMEs. Part 4 presents the results of the survey conducted by the researcher. It aims to identify several behaviors of SMEs with regard to VOIP technology. Also in this chapter, the macro environmental analysis of VOIP implementation in SMEs was discussed using the PEST (Political, Economic, Social and Technological) model. At a latter part of the chapter, the development of a business case for SMEs was presented, including a simple case study on the implementation of the said business case. Part 5 contains the conclusions and recommendations based on the data gathered and discussed in previous chapters. Conclusions were based on data gathered from existing materials and studies made regarding the subject matter, statistical data, survey result, and other relevant materials. Recommendations were based on the conclusions formulated wherein some of the researcher's views and opinions were incorporated.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Small business; Internet telephony